A Minimum Property for Cuboidal Lattice Sums - Cooper, Shaun; Schwerdtfeger, Peter (Symmetry, Integrability and Geometry: Methods and Applications, 2025)
We analyse a family of lattices considered by Conway and Sloane and show that the corresponding Epstein zeta function attains a local minimum for the body-centred cubic lattice.